Secure Coding Practices for Enhancing the Art of Ethical Hacking: A Comprehensive Study - Mohammad Samreen; Manas Kumar Yogi (International Journal of Wireless Security and Networks, 2024)
In the quickly developing scene of network safety, secure coding, and moral hacking are essential for strengthening computerized environments. Secure coding systems and moral hacking are linked to digital strength. This study examines the relationship between secure coding and moral hacking, emphasizing the importance of a hierarchical culture that focuses on secure coding standards. Attention to detail in software development can protect against malicious exploits. Security considerations are integrated throughout the development lifecycle to prevent cyber threats. Expertise in ethical hacking is utilized to uncover code vulnerabilities, highlighting the importance of secure coding practices in risk mitigation within organizations. culture must prioritize secure coding principles and foster collaboration. A combination of defensive and offensive strategies creates a resilient cybersecurity ecosystem. Secure coding practices contribute to the enhancement of ethical hacking. The relationship between secure coding practices and ethical hacking is intertwined with cybersecurity. Secure coding is essential for preventing common vulnerabilities. Threat modeling helps developers design resilient systems. Furthermore, it explores the integration of automated security testing tools, static code analysis, and continuous monitoring to identify vulnerabilities early in the development process, contributing to a more secure codebase. The research examines ethical hacking through penetration testing and red teaming. Ethical hackers can use adversarial knowledge to improve cybersecurity. Secure coding is essential for software resilience. Expanding its purview, the research investigates the application of DevSecOps principles, showcasing how the integration of security measures into the development and operational processes enhances the agility and security posture of software systems. Organizations should focus on security-first mindsets to avoid ethical hacking. Research aims to create a digital landscape that can withstand cyber threats.
Keywords: Encryption; authentication; authorization; coding; security